Is the Open Way a Better Way? Digital Forensics Using Open Source Tools - Manson, D.; Carlin, A.; Ramos, S.; Gyger, A.; Kaufman, M.; Treichelt, J. (2007 40th Annual Hawaii International Conference on System Sciences (HICSS'07), 2007)
The subject of digital forensics can be quite challenging. Digital forensics is in its infancy and teaching digital forensics includes the techniques as well as the tools that assist in the process. This article discusses the tools used in computer forensics, compares an open source tool to two commercial tools, and the advantages and disadvantages of all three tools in an academic environment. A team of four senior students sponsored by two faculty members established the project scope and requirements, presented three prototypes, and detailed the considerations of using open source tools. The same image was used to measure the performance of each software tool. The team found that the three tools provided the same results with different degrees of difficulty. The end results indicate that open source tools are a very good verification of evidence found using other products and should be included in the academic environment